Regulation of Digital Employment Contracts in the Era of Digitalization : Legal and Legal Studies Implications for Worker Protection - Firman Nurdiyansyah Sunandar; Andri Herman Setiawan; Ahmad Juaeni; Johannes Triestanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of digitalization has brought significant changes in various aspects of life, including employment relations. One of the innovations that has emerged is the use of digital employment contracts as a replacement for paper-based contracts. Digital employment contracts offer flexibility and efficiency in modern employment relations. However, in Indonesia, legal regulations related to digital employment contracts still face major challenges, considering the absence of regulations that specifically accommodate this mechanism. Article 52 of Law No. 13 of 2003 concerning Manpower only regulates the requirements for the validity of an employment contract without mentioning the use of electronic documents, while Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE) has recognized the validity of electronic documents. This study aims to analyze the regulation of digital employment contracts in Indonesia, compare them with regulations in other countries, and provide policy recommendations to ensure legal protection for workers in the digitalization era. The method used is a normative legal approach with comparative legal analysis of countries such as the European Union and the United States. The results of the study show that although digital employment contracts are legally valid in Indonesia, there are still legal gaps related to the protection of workers' rights, supervision of implementation, and protection of personal data. Therefore, it is necessary to update regulations that are adaptive to technological developments, including the integration of the principles of justice, legal certainty, and protection of workers' rights in digital employment contracts.